The effect of perceived ease of use and perceived usefulness on reuse intention with e-satisfaction as a mediation variable: Study on SIGNAL application users in Denpasar City - Dewi, Komang Ayu Trishantika; Nurcaya, I Nyoman (International research journal of management, IT and social sciences, 2025)
In the ever-evolving digital era, mobile applications have become an integral part of daily life, including in the management of public services. This study aims to examine the role of e-satisfaction in mediating the influence of perceived ease of use and perceived usefulness on reuse intention based on the technology acceptance model and expectation disconfirmation theory. This study uses a quantitative approach with the causal associative method. The sampling technique used was non-probability sampling, and the number of samples used was 180 users. Data were collected through a Likert scale questionnaire and analyzed using the Structural Equation Modeling method based on Partial Least Squares (PLS-SEM) to test the direct and indirect relationships between variables. The findings of the study show that perceived ease of use and perceived usefulness have a positive and significant effect on reuse intention, perceived ease of use and perceived usefulness have a positive and significant effect on e-satisfaction, and e-satisfaction has a positive and significant effect on reuse intention. The results of the mediation role test showed that e-satisfaction partially mediated the effect of perceived ease of use and perceived usefulness on reuse intention.